Transgender and Non-binary Swimming in the UK: Indoor Public Pool Spaces and Un/Safety - Caudwell, Jayne (Frontiers in Sociology, 2020)
This paper draws from the findings of research that was initiated as a consequence of previous research activities related to University-LGBT+ community physical activity projects (2012-2018). Specifically, the research underpinning this paper centres transgender and non-binary experiences of recreational swimming and aquatic activity (2017-2020). To date, the research has received small amounts of funding from four sources and resulted in two public engagement activities (two art exhibitions). The findings that inform the discussion are taken from nine semi-structured interviews, three focus groups including a professionally drawn illustration of two of these focus groups, and sixty-three research participant’s ‘drawings’ as well as informal conversations with eight stakeholders. The findings concern transgender and non-binary people’s feelings of un/safety in the public spaces of an indoor swimming pool and the accompanying display of their embodied self. These two elements of un/safety—spatiality and embodiment—are critically discussed in relation to physical activity and in/equality. In this way, the work contributes to sustained University-LGBT+ community links and provides possibility for evidenced-based intervention to address inequality.